−3x + 4 - (<span>5x−2)
= </span>−3x + 4 - 5x + 2
= - 8x +6
answer is <span>−8x+6 (first choice)</span>
I believe it’s c ^^
since you multiply the numerators and denominators.. so since the first fraction is 1/2 & the second is 3/4, you’d multiply it like:
1 x 3 & 2 x 4, giving you 3/8.
M=-1
4m+2(m+1)=9m +5
4m+2m+2=9m+5
6m+2=9m+5
6m+2-6m= 9m+5-6m
2-5=3m+5-5
-3/3=3m/3
m=-1
X axis : -t1 cos 60 + t2 cos 60 = 0
t2 cos 60 = t1 cos 60 ; t2 = t1
Y axis : t1 sin 60 + t2 sin 60 - 150 = 0
since t2 = t1
2t1 sin 60 = 150
t1 ( sqrt(3)/2) = 150/2
t1 = 50 [sqrt(3)]
t2 = 50 [sqrt(3)]
t3 = 150 N
hope this helps
3x^2 - 7x + 12 = 0 ....subtract 12 from both sides
3x^2 - 7x = -12 ....divide both sides by 3 to get x^2 by itself
x^2 - 7/3x = -4
His work is not accurate because he divided the second term by 4 instead of 3.